2002
DOI: 10.1046/j.1464-5491.2002.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of von Willebrand factor in plasma in diabetic patients with neuropathic foot ulceration

Abstract: Diabetic patients with neuropathic foot ulceration had severe impairment of cardiac autonomic and peripheral sympathetic nerves. Elevation of vWF in plasma was associated with neuropathic foot ulceration, linking endothelial dysfunction to foot ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…The concept of "vulnerable blood" has been proposed to refl ect the hypercoagulability associated with atherosclerosis and the predominant release of procoagulant factors occurring which characterizes this condition (Naghavi et al 2003). Increased circulating levels of vWF, PAI-1, t-PA, TFPI, and s-TM have been reported in patients with NIDDM (Collier et al 1992;McGill et al 1994;Bagg et al 2001;Aso et al 2002;Leurs et al 2002;Rigla et al 2006). In our study, plasma concentrations of all these markers of endothelial suffering were signifi cantly higher in patients with vascular complications than in control subjects.…”
Section: Discussionsupporting
confidence: 53%
“…The concept of "vulnerable blood" has been proposed to refl ect the hypercoagulability associated with atherosclerosis and the predominant release of procoagulant factors occurring which characterizes this condition (Naghavi et al 2003). Increased circulating levels of vWF, PAI-1, t-PA, TFPI, and s-TM have been reported in patients with NIDDM (Collier et al 1992;McGill et al 1994;Bagg et al 2001;Aso et al 2002;Leurs et al 2002;Rigla et al 2006). In our study, plasma concentrations of all these markers of endothelial suffering were signifi cantly higher in patients with vascular complications than in control subjects.…”
Section: Discussionsupporting
confidence: 53%
“…Laser Doppler studies have shown altered capillary circulation in the feet of patients with DPN ( 42 ). Increased plasma vWF has been associated with neuropathic foot ulceration ( 43 ). In addition to the vasculature, thalamic neurotransmitter mechanisms ( 44 ) and metabolic factors such as Vitamin D ( 45 ) may also play a role in painful-DPN.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of proinflammatory cytokines and adhesion molecules are elevated in patients with diabetes mellitus, linking endothelial dysfunction, atherogenesis and thrombogenesis to foot ulceration, and suggesting a role for systemic inflammation in diabetogenesis (23). Inflammatory activity can promote vascular injury by modifying lipoprotein structure and function, changing the composition of plasma proteins and causing alterations in the vascular endothelium (34,35). No clear correlation between the measured endothelial‐specific parameters and the extent of wound healing was found in this investigation.…”
Section: Discussionmentioning
confidence: 99%